Deteksi Dini Potensi Kebangkrutan Bank dengan Model Grover - Aprilia Nur Aeni (Jurnal Ilmu Manajemen, 2020)
Bankruptcy is a condition when a company experiences insufficient funds to run its business. Prediction of potential bankruptcy is very important because of the need for early indications from banks using internal factors as well as external factors. One of them uses financial statements to minimize the risk of bank failure. This study aims to analyze the effect of Return on Assets (ROA), Capital Adequacy Ratio (CAR), Net Performing Loan (NPL), (BOPO), Firm size, Market Effect on the potential bankruptcy of the bank using the model Grover. The total population used was 45 banks and the sample taken in this study were 37 banks listed on the Indonesia Stock Exchange in the 2015-2018 period with a purposive sampling method. This research is causality research with the method of data collection using documentation, namely by taking data from the company's annual report. The data analysis method uses descriptive statistical analysis and logistic regression analysis. The results showed that the Return on Assets (ROA) ratio, Capital Adequacy Ratio (CAR), Firm size, Market Effect have a positive and not significant relationship to bankruptcy potential. Whereas the Net Performing Loan (NPL) ratio, Operational Expense to Operating Income (BOPO) has a negative and insignificant relationship to the bank's potential bankruptcy. This is because the average variable value is above the criteria of Indonesian banks, and banks listed on the Indonesian stock exchange can maintain well. This indicates that the Grover model is accurate in measuring the health of banks.